Prof. M. J. Koncen's quadrille call book and ball room guide; to which is added a sensible guide to etiquette and deportment in the ball and assembly room. Ladies toilet, gentleman's dress, etc. etc. and general information for dancers ... - Koncen, M. J. (Mathias J.) (St. Louis, Press of S. F. Brearley & Co., 1883)
This manual is a compilation of previously published materials and includes standard advice on etiquette and dress. Dances include the grand march, quadrilles, and numerous round dances such as the waltz, glide waltz, Boston dip, society waltz, knickerbocker waltz, and the Newport. The popular series of party games called the German (also known as the cotillon) is given sixty-eight figures, and other group dances include the "Virginia Reel."
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals